Hydrogen Bistability as the Origin of Photo‐Bias‐Thermal Instabilities in Amorphous Oxide Semiconductors. (8th May 2015) - Kang, Youngho; Ahn, Byung Du; Song, Ji Hun; Mo, Yeon Gon; Nahm, Ho‐Hyun; Han, Seungwu; Jeong, Jae Kyeong
<x xml:space="preserve">Abstract</x> Zinc‐based metal oxide semiconductors have attracted attention as an alternative to current silicon‐based semiconductors for applications in transparent and flexible electronics. Despite this, metal oxide transistors require significant improvements in performance and electrical reliability before they can be applied widely in optoelectronics. Amorphous indium–zinc–tin oxide (a‐IZTO) has been considered an alternative channel layer to a prototypical indium–gallium–zinc oxide (IGZO) with the aim of achieving a high mobility (>40 cm2 Vs−1) transistors. The effects of the gate bias and light stress on the resulting a‐IZTO field‐effect transistors are examined in detail. Hydrogen impurities in the a‐IZTO semiconductor are found to play a direct role in determining the photo‐bias stability of the resulting transistors. The Al2O3‐inserted IZTO thin‐film transistors (TFTs) are hydrogen‐poor, and consequently show better resistance to the external‐bias‐thermal stress and photo‐bias‐thermal stress than the hydrogen‐rich control IZTO TFTs. First‐principles calculations show that even in the amorphous phase, hydrogen impurities including interstitial H and substitutional H can be bistable centers with an electronic deep‐to‐shallow transition through large lattice relaxation. The negative threshold voltage shift of the a‐IZTO transistors under a negative‐bias‐thermal stress and negative‐bias‐illumination stress condition is attributed to the transition from the acceptor‐like deep interstitial Hi− (or substitutional H‐DX−) to the shallow Hi+ (or HO+) with a high (low) activation energy barrier. Conclusively, the delicate controllability of hydrogen is a key factor to achieve the high performance and stability of the metal oxide transistors.